Addressing Australia's collaboration 'problem': Is there a Brave New World of innovation policy post COVID‐19?. Issue 2 (9th March 2021) - George, AJ; Tarr, Julie‐Anne
Abstract: In a post‐COVID‐19 world, innovation stimuli and well‐aligned policies will assume even greater importance as various sectors seek to recover lost ground and to generate new opportunities. Collaborative partnering in innovation research and development (R&D) between private industry and higher education has increasingly emerged over the last decade as a leading key performance indicator for government policy development, and higher education research funding allocations. Recalibration of R&D‐related policies and incentivisation will require careful consideration, with constructive lessons to be learned from outcomes over the last four decades. This paper presents findings from a new study of stakeholder perceptions as to the National Innovation and Science Agenda's impact on innovation partnerships, and synthesises outcomes from two prior studies. It then examines a newly proposed innovation policy framework, Stimulating Business Investment in Innovation (SBII), set against a background of the shifting mix of paradigms that have comprised Australian innovation policy over the last 40 years. It argues that, following the SBII, any proposed change of policy direction will face significant challenges in its implementation, requiring a fully committed and comprehensive embrace by Government of the new APS engagement framework and greater levels of deliberative democracy. Abstract : Industry–research partnering is a key performance indicator for government policy and research funding. This Paper synthesizes three studies on innovation, set against the shifting mix of paradigms in innovation policy over the last 40 years. Policymakers must embrace the new engagement framework, and deliberative democracy, when adopting new innovation policy.